Flypaper Effect of Regional Expenditures in Yogyakarta - Muh Rudi (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
One of the consequences as aÂ result of the implementation of regional autonomy is that local governments must have sufficient financial resources to pay their autonomy government. The financial capacity of local governments would determine the ability of local governments to perform the functions of government. Considering Article 5 of Law No. 33, 2004, sources of regional revenue are regional revenues, balance funds/ transfers and financing. When local revenue comes from the transfers, the stimulation of expenditure is different from the stimulation that arises from local revenue (especially local taxes). This study focuses on identifying the flypaper effect on expenditure areas and its classification with samples of five districts and cities in Yogyakarta during 2006-2015. This paper argued that during the period among flypaper did not occur in the expenditure area and sub expenditure areas. In addition, flypaper found only in capital expenditure, while expenditure is not a suspect.Â Keywords: flypaper, autonomy and fiscal needs, local autonomy,Â Yogyakarta